THE EFFECT OF CALL CENTER 110 SERVICE QUALITY ON PUBLIC SATISFACTION IN WEST TULANG BAWANG REGENCY - V. Saptarini; Erwan Sujana (RADJA PUBLIKA, 2026)
This study examines the effect of service quality delivered through the Indonesian National Police Call Center 110 on public satisfaction in West Tulang Bawang Regency. The research was motivated by variations in response speed, completion time, facility adequacy, and officer responsiveness reported by service users. An explanatory quantitative survey was conducted among 100 household heads selected through simple random sampling across nine districts. Data were collected using two ten-item Likert instruments measuring service quality and public satisfaction. All items were valid; Cronbach’s alpha values were 0.900 for service quality and 0.928 for public satisfaction. Descriptive results placed service quality at 72.68% and public satisfaction at 73.90%, both in the agree category. Simple linear regression produced Y = 23.277 + 0.376X, with R = 0.425 and R² = 0.181. The service-quality coefficient was positive and statistically significant (t = 4.652; p < 0.001). The findings indicate that better operator conduct, competence, communication, responsiveness, confidentiality, facilities, and service accuracy increase public satisfaction. Improvements should prioritize fast and precise responses and fair treatment for every caller.